2023
DOI: 10.1021/acs.orglett.3c00049
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced N-Heterocyclic Nitrenium-Catalyzed Single Electron Reduction of Acyl Fluorides for Phenanthridine Synthesis

Abstract: Acyl fluorides are versatile reagents in organic synthesis. However, there is no precedent to employ acyl fluorides as acyl radical precursors. We herein report an N-heterocyclic nitrenium iodide salt-catalyzed photoreduction of acyl fluorides to produce acyl radicals, which could react with 2-isocyanobiaryls to afford various carbonyl phenanthridines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…[27,29] Typically, photochemical methods are effectively used for reactions involving radical pathways to form CÀ C coupling or carbon-heteroatom bonds. [30][31][32][33][34][35][36][37][38] However, photochemical reactions often require expensive photocatalysts such as complexes of Ir or Ru metals or dye compounds. [39][40][41][42] Therefore, it is useful to develop novel photocatalyst-free photochemical reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27,29] Typically, photochemical methods are effectively used for reactions involving radical pathways to form CÀ C coupling or carbon-heteroatom bonds. [30][31][32][33][34][35][36][37][38] However, photochemical reactions often require expensive photocatalysts such as complexes of Ir or Ru metals or dye compounds. [39][40][41][42] Therefore, it is useful to develop novel photocatalyst-free photochemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Light energy can activate substrates and produce organic reactions under mild conditions [27,29] . Typically, photochemical methods are effectively used for reactions involving radical pathways to form C−C coupling or carbon‐heteroatom bonds [30–38] . However, photochemical reactions often require expensive photocatalysts such as complexes of Ir or Ru metals or dye compounds [39–42] .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, visible-light-induced photocatalysis has emerged as a green and sustainable route with high synthetic potential . The generation of acyl radicals at room temperature under mild conditions has been made possible by utilizing photoredox strategies .…”
Section: Introductionmentioning
confidence: 99%
“…This form demonstrates a nitrogen nonoctet character in these ions, which possess a relatively low LUMO and a free p-orbital on the central N-atom. These unique properties of NHNs allowed us and others to demonstrate that NHNs can act as nitrogen-based Lewis acids, [29][30][31][32][33] activators of strong bonds through frustrated Lewis pair chemistry, 30,34 catalytic Lewis acids for several reactions, [35][36][37][38] photocatalysts [39][40][41] and a platform for stable nitrogen-based radicals. 42,43 Exploring this Lewis acidity, we previously demonstrated that NHN 1 reacts with phenyllithium or n-butyllithium to furnish cyclic triazanes 2 (Scheme 2b).…”
Section: Introductionmentioning
confidence: 99%